2008
DOI: 10.1007/s12122-008-9054-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Minimum Wage Increases on Retail Employment and Hours: New Evidence from Monthly CPS Data

Abstract: Minimum wage, Employment, Retail trade,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 21 publications
(52 reference statements)
2
43
0
1
Order By: Relevance
“…Much of the literature examining the employment effects of minimum wage increases has focused on low-skilled workers, usually teenagers and high school dropouts, or on workers in low-skilled industries because these populations are more likely to be affected by such increases. Neumark and Wascher (2007) review over 90 studies published since the iconoclastic Card andKrueger (1994, 1995) studies of the mid-1990s and conclude that there is overwhelming evidence that the least-skilled workers experience the strongest disemployment effects from minimum wage increases (see, for example, Neumark and Wascher 1992;Williams 1993;Deere, Murphy, and Welch 1995;Currie and Fallick 1996;Abowd et al 1999;Partridge and Partridge 1999;Burkhauser, Couch, and Wittenburg 2000a, b;Couch and Wittenburg 2001;Neumark 2001;Neumark andWascher 2002, 2004;Campolieti, Fang, and Gunderson 2005;Campolieti, Gunderson, and Riddell 2006;Sabia 2008Sabia , 2009a. Median employment elasticities range from 20.1 to 20.3, though a few studies have found employment elasticities that are larger (between 20.6 and 20.9) for less-educated single mothers (Sabia 2008) and younger high school dropouts (Burkhauser, Couch, and Wittenberg 2000b).…”
Section: Employment and Hours Worked Effects Of Minimum Wage Increasesmentioning
confidence: 99%
“…Much of the literature examining the employment effects of minimum wage increases has focused on low-skilled workers, usually teenagers and high school dropouts, or on workers in low-skilled industries because these populations are more likely to be affected by such increases. Neumark and Wascher (2007) review over 90 studies published since the iconoclastic Card andKrueger (1994, 1995) studies of the mid-1990s and conclude that there is overwhelming evidence that the least-skilled workers experience the strongest disemployment effects from minimum wage increases (see, for example, Neumark and Wascher 1992;Williams 1993;Deere, Murphy, and Welch 1995;Currie and Fallick 1996;Abowd et al 1999;Partridge and Partridge 1999;Burkhauser, Couch, and Wittenburg 2000a, b;Couch and Wittenburg 2001;Neumark 2001;Neumark andWascher 2002, 2004;Campolieti, Fang, and Gunderson 2005;Campolieti, Gunderson, and Riddell 2006;Sabia 2008Sabia , 2009a. Median employment elasticities range from 20.1 to 20.3, though a few studies have found employment elasticities that are larger (between 20.6 and 20.9) for less-educated single mothers (Sabia 2008) and younger high school dropouts (Burkhauser, Couch, and Wittenberg 2000b).…”
Section: Employment and Hours Worked Effects Of Minimum Wage Increasesmentioning
confidence: 99%
“…Our approach differs from that of Sabia (2008) in at least two important ways. First, we use more complete data on employment in retail trade by using countylevel counts of employment from the Quarterly Census of Employment and Wages.…”
Section: The Previous Literature On Minimum Wages In the Retail Sectormentioning
confidence: 99%
“…10 Since the information in this column pertains to the number of counties that meet the balanced panel restriction of having data available throughout the 64 quarters, the number of quarterly observations utilized for each sector is simply the number of counties multiplied by 64. 11 Sabia (2008) also considered the importance of state-level trends in his analysis, finding that accounting for these trends no longer provided evidence of a disemployment effect in the retail sector. Neumark and Wascher (2007) found that adding state-level trends tended to lead to insignificant minimum wage coefficients, although this seems partly due to the increase in standard errors caused by this inclusion.…”
Section: Empirical Specificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Because the inclusion of year effects in Equation (1) will capture much of the variation in federal minimum wages, state minimum wage changes provide an important source of identifying variation. In particular, the post-1997 period provides a rich new source of identification because of the increase in both frequency and magnitude of state minimum wage hikes (Sabia, 2008a). Wittenburg (2000a, 2000b), Card and Krueger (1995), and Deere, Murphy, and Welch (1995), several state-and year-specific measures of economic health are included as controls.…”
Section: Datamentioning
confidence: 99%